Associations between Trauma Exposure and Physical Conditions among Public Safety Personnel: Associations entre l'exposition à un traumatisme et les problèmes physiques chez le personnel de la santé publique. (August 2020) - Sommer, Jordana L.; El-Gabalawy, Renée; Taillieu, Tamara; Afifi, Tracie O.; Carleton, R. Nicholas
Background: Trauma exposure is associated with adverse health-related correlates, including physical comorbidities, and is highly prevalent among public safety personnel (PSP). The current study (1) examined the association between context of index trauma exposure (part of job vs. other) and physical conditions and (2) established the prevalence of physical conditions according to PSP category (e.g., police, paramedic) and index trauma type (e.g., serious accident, physical assault) in a large Canadian sample of PSP. Methods: PSP completed an online survey between September 2016 and January 2017. Multivariable logistic regressions examined associations between context of index trauma exposure (i.e., part of job vs. other) and physical condition categories. Cross-tabulations with chi-square analyses examined whether the prevalence of physical conditions significantly differed according to PSP category and index trauma type. Results: There were 5, 267 PSP included in the current study. Results from the most stringent model of logistic regressions demonstrated that, compared to PSP who experienced their index trauma in any other context, PSP who experienced it as part of their job had reduced odds of "other" physical conditions (adjusted odds ratio = 0.73, 95% confidence interval, 0.57 to 0.94, P < 0.05). Results also revealed significant differences in the prevalence of physical conditions across all PSP categories and select index trauma types. Conclusion: Results highlight the relevance of trauma exposure outside of an occupational context among PSP and may have implications for the positive impact of stress inoculation and resiliency training programs for PSP.